2015
DOI: 10.4338/aci-2014-08-ra-0065
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medicine Resident Physicians’ Perceptions of Electronic Documentation and Workflow

Abstract: SummaryObjective: To understand emergency department (ED) physicians' use of electronic documentation in order to identify usability and workflow considerations for the design of future ED information system (EDIS) physician documentation modules. Methods: We invited emergency medicine resident physicians to participate in a mixed methods study using task analysis and qualitative interviews. Participants completed a simulated, standardized patient encounter in a medical simulation center while documenting in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
1
24
0
1
Order By: Relevance
“…11 Additionally, Neri et al reported that emergency physicians struggle to integrate clinical data from disparate sources into their clinical documentation workflows which occupy a significant portion of their work. 39 Given the significance of chart review and data integration for physicians, dashboards are uniquely poised to facilitate these tasks by providing tailored data aggregation and potentially reducing cognitive load. Furthermore, dashboard aggregation has also been shown to reduce medication errors at the point of care, 40 suggesting that the benefits of such dashboards may extend beyond EHR work reductions to include clinical benefits as well.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, Neri et al reported that emergency physicians struggle to integrate clinical data from disparate sources into their clinical documentation workflows which occupy a significant portion of their work. 39 Given the significance of chart review and data integration for physicians, dashboards are uniquely poised to facilitate these tasks by providing tailored data aggregation and potentially reducing cognitive load. Furthermore, dashboard aggregation has also been shown to reduce medication errors at the point of care, 40 suggesting that the benefits of such dashboards may extend beyond EHR work reductions to include clinical benefits as well.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Resident physicians report spending more time in reading and documenting medical health records than being at the bedside and raise concerns over the lack of feedback on their charting. 18 19 One solution is to encourage, teach and provide incentives for improving the quality of health records to avoid losing important messages in the noise. 20 Specifically, data from the USA demonstrate that physicians do not receive adequate training in disease nosology and coding methods.…”
Section: Discussionmentioning
confidence: 99%
“…[22] The authors stated that the use of a passive alert led to the low impact, but weighed the advantages of an active alert against the potential for ‘alert fatigue.’ The complex task of clinical decision support design should be addressed through user-centered design. [23]…”
Section: Introductionmentioning
confidence: 99%